Empowering Students to Be Changemakers: Activist Pedagogy in a Democratic School - Parker-Shandal, Crystena (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Activist approaches to teaching resist neoliberal and white-centric approaches to education. Within such a framework, students can develop racial literacy and civic identity as activist citizens. In this case study of one classroom in a publicly funded democratic school, the teacher used activist pedagogy — an approach that directly engages young people with real-world injustices and supports them to take action — to weave together restorative pedagogy, racial literacy, and elements of critical race theory. The teacher’s practices illustrate how these theoretical perspectives, when combined, can nurture students’ sense of justice and equity. Drawing on classroom observations, interviews, and students’ written/artistic works, the article highlights how children in a mixed-grade class (ages 9–11) used critical inquiry and activism to advocate for social change. Even within a neoliberal system of schooling, this study shows the potential of a holistic, activist-oriented framework to empower young people to see themselves as capable of transforming the world around them.